2020
DOI: 10.1534/g3.120.401718
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Resolving Asthma Molecular Signatures Using Tissue-Specific Transcriptome Data

Abstract: An integrative analysis focused on multi-tissue transcriptomics has not been done for asthma. Tissue-specific DEGs remain undetected in many multi-tissue analyses, which influences identification of disease-relevant pathways and potential drug candidates. Transcriptome data from 609 cases and 196 controls, generated using airway epithelium, bronchial, nasal, airway macrophages, distal lung fibroblasts, proximal lung fibroblasts, CD4+ lymphocytes, CD8+ lymphocytes from whole blood and induced sputum samples, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Interestingly, machine learning (support vector machines) showed that differences between asthma and control samples were more discriminatory in macrophages than in the epithelial cells. We found little overlap between the genes that were overexpressed to the highest degree in the ileum of asthma patients, and asthma-specific genes identified across tissues by Ghosh et al [ 37 ]. However, a transcriptomic study of airway epithelial cells by Kicic et al revealed that the response to a biotic stimulus was the top upregulated pathway in asthma [ 38 ], and this theme was also enriched in the ileum.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Interestingly, machine learning (support vector machines) showed that differences between asthma and control samples were more discriminatory in macrophages than in the epithelial cells. We found little overlap between the genes that were overexpressed to the highest degree in the ileum of asthma patients, and asthma-specific genes identified across tissues by Ghosh et al [ 37 ]. However, a transcriptomic study of airway epithelial cells by Kicic et al revealed that the response to a biotic stimulus was the top upregulated pathway in asthma [ 38 ], and this theme was also enriched in the ileum.…”
Section: Discussionmentioning
confidence: 56%
“…A large integrative study of asthma transcriptomics in various tissues [ 37 ] revealed organism-wide changes in IL-1β and ERK signaling. Airway samples in asthma have dysregulated TGFβ, as well as IL-13.…”
Section: Discussionmentioning
confidence: 99%
“…Inherent gene expression due to potential confounders produced from highly expressed genes in different tissue or cell types might be ignored in an analysis of DEGs in a single source. Recently, some gene expression studies on asthma [ 36 ], musculoskeletal development [ 37 ], and nonalcoholic fatty liver disease [ 38 ] have reported approaches in which different tissues were combined.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive work has compared the similarity of gene expression in the human bronchial and nasal epithelium ( Deprez et al, 2020 ; Ghosh et al, 2020 ; Nguyen et al, 2018 ). This relationship is important both in the context of the healthy and diseased airways, the response to bacterial or viral infection, and the development of therapeutics for airway disease.…”
Section: Discussionmentioning
confidence: 99%